TINJAUAN HUKUM ISLAM TERHADAP HAK KEAGAMAAN PENYANDANG DISABILITAS DALAM UNDANG-UNDANG RI NO 8 TAHUN 2016 DAN PENERAPANNYA DI KOTA PADANG - Rosa Marlina; Sobhan Sobhan; Elfia Elfia (UIN Imam Bonjol Padang, 2021)
This paper aims to find out the review of Islamic law on the religious rights of persons with disabilities in the RI Law No. 8 of 2016 and its application in the city of Padang. This research is a field research. Data collected through interviews conducted in the city of Padang, namely the Office of the Ministry of Religion of the city of Padang, the Office of the Mayor of Padang, the Social Service of the city of Padang. The results of this study are the review of Islamic law on the religious rights of persons with disabilities in Law No. 8 of 2016 does not conflict with Islam, while the application of the religious rights of persons with disabilities, especially those who adhere to Islam in the city of Padang has not been maximally fulfilled with facilities that have not been fully implemented. inadequate and inadequate aspects of services for persons with disabilities and human resources that have not been maximized in teaching Islamic religious education.